2014
DOI: 10.1186/s12916-014-0168-4
|View full text |Cite
|
Sign up to set email alerts
|

Combined impact of healthy lifestyle factors on colorectal cancer: a large European cohort study

Abstract: BackgroundExcess body weight, physical activity, smoking, alcohol consumption and certain dietary factors are individually related to colorectal cancer (CRC) risk; however, little is known about their joint effects. The aim of this study was to develop a healthy lifestyle index (HLI) composed of five potentially modifiable lifestyle factors – healthy weight, physical activity, non-smoking, limited alcohol consumption and a healthy diet, and to explore the association of this index with CRC incidence using data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
159
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 201 publications
(182 citation statements)
references
References 40 publications
(53 reference statements)
9
159
0
14
Order By: Relevance
“…Another approach is to define a priori clusters based on the number of risk behaviours. This methodology has shown that unhealthy lifestyle behaviours cumulatively increase the risk of cardiovascular disease, cancer and premature death in adult populations [32,33,34]. Sanchez and collaborators [15] observed a cumulative effect of low physical activity, high television viewing, high fat intake and low fruit and vegetable consumption on the risk of overweight in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach is to define a priori clusters based on the number of risk behaviours. This methodology has shown that unhealthy lifestyle behaviours cumulatively increase the risk of cardiovascular disease, cancer and premature death in adult populations [32,33,34]. Sanchez and collaborators [15] observed a cumulative effect of low physical activity, high television viewing, high fat intake and low fruit and vegetable consumption on the risk of overweight in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Les CCR occupent le troisième rang des cancers malins en termes d'incidence et de mortalité [2]. À l'heure actuelle, on ne connaît pas la cause de la formation et le développement des adénomes, on sait toutefois que le tabagisme, l'alimentation riche en graisses et pauvre en fibres alimentaires, la consommation excessive d'alcool et la surcharge pondérale sont des facteurs de risque [3]. En Algérie, l'incidence des CCR demeure faible par rapport aux pays développés, en dépit du fait qu'elle est en constante augmentation.…”
Section: Introductionunclassified
“…La alimentación y los hábitos alimentarios influyen sobre tres etapas del cáncer -riesgo, prevención (7,8) y pronóstico (9)-, siendo la relación entre dieta y riesgo de padecer la enfermedad la más conocida (9)(10)(11). Se han publicado numerosos estudios epidemiológicos que relacionan el consumo de fibra y carnes rojas con el desarrollo del CCR, así como estudios a nivel molecular que esclarecen su relación con la carcinogénesis (11,12).…”
Section: Introductionunclassified